Chitosan grafted with a heteropolyanion-based ionic liquid as an effective and reusable catalyst for acetalization. Issue 47 (26th April 2016) - Zhang, Wei-Hong; Liu, Shan-Shan; Liu, Ping; Xu, Jie; Xue, Bing; Wei, Xian-Yong; Li, Yong-Xin
Abstract : Chitosan grafted with a heteropolyanion-based ionic liquid (CS–VImPS–PW) was developed via a radical addition and subsequent acidification reaction. It proved to be a green, effective and recyclable catalyst for various acetalization reactions. Abstract : Chitosan immobilized with an acidic ionic liquid (CS–VImPS–PW) was fabricated via a radical addition reaction of N -vinylimidazoliumpropane sulfonate and chitosan, followed by acidification with a heteropolyacid. It was characterized by a Fourier transform infrared spectrometer, solid-state 13 C nuclear magnetic resonance spectrometer, thermogravimetric analyzer, elemental analyzer, and Hammett indicator. Some acetalization reactions were investigated to evaluate the catalytic activity of CS–VImPS–PW. The results show that CS–VImPS–PW is highly active for the acetalization reactions in high acetal yields ranging from 83.2 to 96.2% and can be reused 8 times without noticeable loss of activity.